THE INFLUENCE OF THE IMPLEMENTATION OF ISO 9000: 2008 AND ENVIRONMENTAL ACCOUNTING ON COMPANY PERFORMANCE IN CHEMICAL SECTORS IN 2016 TO 2018 - Arya Darmawan (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2021)
The purpose of this study is to empirically prove the influence of the application of ISO and environmental accounting on company performance in chemical sector companies in 2016 to 2018. The research method used is quantitative descriptive method. The research data was taken from the Indonesia Stock Exchange (IDX) in the form of annual reports for the period 2016 to 2018. Testing the hypothesis of this study used multiple regression analysis because the independent variables used dummy measurements. This study uses SPSS software version 21. The results of the study simultaneously found that ISO 9000: 2008 and environmental accounting have a positive effect on company performance.